Improvements of C–H Radio-Iodination of N-Acylsulfonamides toward Implementation in Clinics - Dubost, Emmanuelle; Babin, Victor; Benoist, Florian; Hébert, Alexandra; Pigrée, Gilbert; Bouillon, Jean-Philippe; Fabis, Frédéric; Cailly, Thomas (Synthesis, 2019)
An improved protocol to perform C–H radio-iodination is described. These new conditions allow rapid and clean formation of radio-iodinated N-acylsulfonamides using [125I]NIS and catalytic amounts of palladium acetate and para-toluenesulfonic acid. No pre-functionalized precursors are required and the products are obtained with radiochemical conversions (RCC) of 27–84%.
Keywords: radiochemistry; iodination; C–H activation; palladium; iodine-125